2017
DOI: 10.1111/eth.12624
|View full text |Cite
|
Sign up to set email alerts
|

Alarm call‐based discrimination between common cuckoo and Eurasian sparrowhawk in a Chinese population of great tits

Abstract: Morphological resemblance of the common cuckoo Cuculus canorus to the Eurasian sparrowhawk Accipiter nisus has been regarded as an example of predator mimicry. Common hosts could distinguish parasites as the result of coevolution, while rare hosts or nonhosts may mistake cuckoos for hawks because rare hosts or non-hosts behave similarly when faced with these two species. Birds usually produce alarm calls in addition to showing behavioral responses when in danger. However, previous studies of identification by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 62 publications
0
41
0
Order By: Relevance
“…We decided to group breeding and nonbreeding gregarious species, because we assumed that social cognition, that is, the capacity to communicate with other individuals belonging to the same species, is a species-specific trait that may be manifest all the time (Yu et al, 2016(Yu et al, , 2017. We decided to group breeding and nonbreeding gregarious species, because we assumed that social cognition, that is, the capacity to communicate with other individuals belonging to the same species, is a species-specific trait that may be manifest all the time (Yu et al, 2016(Yu et al, , 2017.…”
Section: Ecological Variables: Gregariousness Trophic Guild and Bmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to group breeding and nonbreeding gregarious species, because we assumed that social cognition, that is, the capacity to communicate with other individuals belonging to the same species, is a species-specific trait that may be manifest all the time (Yu et al, 2016(Yu et al, , 2017. We decided to group breeding and nonbreeding gregarious species, because we assumed that social cognition, that is, the capacity to communicate with other individuals belonging to the same species, is a species-specific trait that may be manifest all the time (Yu et al, 2016(Yu et al, , 2017.…”
Section: Ecological Variables: Gregariousness Trophic Guild and Bmentioning
confidence: 99%
“…There was a positive correlation between gregariousness during these two periods (Kendall rank order correlation τ = 0.40, p = 0.020), implying that species that were gregarious during breeding also tend to be gregarious during the nonbreeding season. We decided to group breeding and nonbreeding gregarious species, because we assumed that social cognition, that is, the capacity to communicate with other individuals belonging to the same species, is a species-specific trait that may be manifest all the time (Yu et al, 2016(Yu et al, , 2017.…”
Section: Ecological Variables: Gregariousness Trophic Guild and Bmentioning
confidence: 99%
“…When Japanese Tits face avian predators, D notes can be produced alone or in combination with other notes that appear as note strings at the end of a call (Suzuki 2014). Yu et al (2017) also found that portions of the alarm calls of Japanese Tits in response to the Common Cuckoo contained D-note strings, and the tits even produced more D-type notes and fewer I-type notes per call when responding to Sparrowhawks than to cuckoos.…”
Section: Open Accessmentioning
confidence: 81%
“…Japanese Tits produce alarm calls in response to predators, as reported by Suzuki (2012), as well as in response to the Common Cuckoo (Yu et al 2017). Furthermore, Suzuki (2014) demonstrated that Japanese Tits could alter the calling rate, note number and note combinations in alarm calls in response to martens and crows; for example, they produced more D notes for martens than for crows.…”
Section: Open Accessmentioning
confidence: 90%
See 1 more Smart Citation